Effect of Gender and Academic Disciplines on Narcissism, Emotional Intelligence, Empathy and Impulsivity - Arora, Rhythm (My University, 2024)
The present study investigates the effect of gender and academic disciplines on narcissism, empathy, emotional intelligence and impulsivity. The data was collected from 200 participants from two disciplines, 120 from engineering and 80 from liberal arts. There were 60 males and females and 40 males and females from engineering and liberal arts disciplines, respectively. The age group which was required for the collection of the data was 18-30 years. The tools used for the purpose described above were the Narcissism Personality Inventory (NPI), The Toronto Empathy Questionnaire (TEQ), Trait Emotional Intelligence Questionnaire – Short Form (TEIQue-SF) and Go/No Task. Descriptive Statistics and ANOVA were computed to calculate the results for the obtained data. The results revealed that there was a significant difference in narcissism and impulsivity between engineering and liberal arts disciplines. Also, there was an interaction effect between academic disciplines and gender on narcissism.
Keywords: Narcissism; Empathy; Emotional Intelligence; Liberal Arts; Engineering students; EI; Impulsivity